Research advances in the pathogenesis and therapeutic interventions of Helicobacter pylori and atrial fibrillation - Wang, Zhaofen; Wang, Haijuan; Yan, Yi; Chang, Peng (Frontiers in Cardiovascular Medicine, 2025)
Atrial fibrillation (AF) has emerged as a global health challenge in the 21st century. As the most common clinical arrhythmia, AF is characterized by high rates of recurrence, disability, and mortality, coupled with substantial healthcare expenditures. Despite significant advancements in AF management in recent years, the etiological drivers and pathogenic mechanisms remain incompletely understood in a subset of patients. Since the association between Helicobacter pylori (H. pylori) infection and non-gastrointestinal diseases was reported, H. pylori-associated non-gastrointestinal diseases have gradually attracted a lot of attention, especially in cardiovascular diseases. Nevertheless, studies on the relationship between H. pylori infection and AF are still limited, and the results are controversial. Rigorous large-scale studies are warranted to delineate the pathophysiological interplay between H. pylori colonization and AF pathogenesis, with particular emphasis on determining whether eradication therapy reduces AF-associated cardiovascular morbidity or enhances long-term patient outcomes. In view of this, the aim of this paper is to review the role of H. pylori in the occurrence and development of AF, to analyze the relationship between H. pylori-related cardiovascular diseases, non-cardiovascular diseases, and AF, and to explore the possible pathogenesis so as to provide new ideas and research directions for the treatment of AF, especially the intervention of idiopathic AF(iAF).